The - Flinders, Steve (Oxford University Press, 2001)
This full-color series presents nonfiction topics about interesting places and subjects. Each title features color photographs and a glossary to help with vocabulary comprehension. Exercises and suggestions for project work are also included. The books are graded at 400-to 1,400-word vocabulary levels. Audio "CDs or "Cassettes are available for select titles